2013
DOI: 10.1159/000346336
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal Thickness: Does It Have an Impact on Outcomes of Percutaneous Nephrolithotomy?

Abstract: Objective: To evaluate whether renal parenchymal thickness (RPT) has an effect on the outcomes of percutaneous nephrolithotomy (PNL). Methods: We performed a retrospective analysis of 144 patients with lower pole and/or renal pelvic stones who underwent PNL. The relationship between RPT and peri- and postoperative measures was evaluated. Results: The average age was 45.94 ± 14.47 (15-76) years. The mean BMI was calculated as 27.47 ± 4.73 (16.9-44.9) kg/m2. The mean stone burden was 293 ± 126 (150-80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Similar findings were shown in a study with a smaller patient number done by Sergeyev et al [16]. In their study where the effect of renal parenchymal thickness on PCNL was evaluated, Tepeler et al [7] found that with the increase in renal parenchymal thickness, the decrease in hemoglobin increased but the blood transfusion rate remained unchanged. Wang et al [22] also demonstrated that a thick renal parenchyma without hydronephrosis was a risk factor for severe bleeding after PCNL.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Similar findings were shown in a study with a smaller patient number done by Sergeyev et al [16]. In their study where the effect of renal parenchymal thickness on PCNL was evaluated, Tepeler et al [7] found that with the increase in renal parenchymal thickness, the decrease in hemoglobin increased but the blood transfusion rate remained unchanged. Wang et al [22] also demonstrated that a thick renal parenchyma without hydronephrosis was a risk factor for severe bleeding after PCNL.…”
Section: Discussionsupporting
confidence: 77%
“…It was supported by other studies with smaller patient numbers [16,17 ]that obesity does not have an influence on stone-free rates after PCNL. In another study assessing the effects of renal parenchymal thickness on PCNL outcomes, no relationship between renal parenchymal thickness and the success of operation was found [7]. In our study, patients were evaluated by being grouped according to SSD, which is influenced by obesity and renal parenchymal thickness.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations